Genotypes and clinical intervention of patients with neurofibromatosis type 1 associated dystrophic scoliosis - Li, Haichong; Zhang, Wenyan; Yao, Ziming; Guo, Ruolan; Hao, Chanjuan; Zhang, Xuejun (Frontiers in Pediatrics, 2022)
Objective To analyze the genotypic characteristics of patients with neurofibromatosis type 1 (NF1) associated dystrophic scoliosis and to summarize the outcomes of the surgical treatment of these patients. Methods Exome sequencing (ES) combined with multiplex ligation-dependent probe amplification (MLPA) was used for genotypic identification. All patients underwent surgical treatments for spinal deformities, and the outcomes of the surgery was summarized by analyzing the clinical and imaging parameters before and after the surgery. Results Fourteen patients (six males and eight females) were clinically diagnosed as NF1 associated dystrophic scoliosis with common symptoms including café-au-lait spots, paravertebral tumors, and dystrophic scoliosis. NF1 mutations were detected in 12 (85.7%) patients, including four nonsense mutations, three splicing mutations, three frameshift mutations, and two exon deletions. The first surgical procedure included growing-rod surgery in 10 patients and posterior spinal fusion in four patients. The follow-up duration was 2.3 years (1.0–10.3 years), and the Cobb angle of the main curve improved from 61.5° (30°-125°) pre-operatively to 14.5° (0°-42°) at the last follow-up, with an average correction rate of 74.0% (44–100%). Instrumentation-related complications occurred in four patients during the follow-up period. Conclusions In patients with dystrophic scoliosis who met the clinical diagnostic criteria for NF1, the mutation detection rate of ES combined with MLPA was 85.7%. There was no mutation hotspot in NF1 gene, molecular diagnosis could offer information about genetic counseling, prenatal diagnosis and eugenics. Surgical treatment according to patient's age and severity could effectively correct the spinal deformities.